Analysis of Product Variation, Quality of Service and Their Effect on Customer Satisfaction - Suarni Norawati; Arman Arman; Auzar Ali; Amri Ihsan; Eka Putra (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This research aims to determine the effect of either partially or simultaneously of the variable product variation and service quality on customer satisfaction Design/methodology/approach: The data used of primary data which obtained by questionnaire, observation, interview and documentation methods. The sample is 96 customers done by accidental sampling method. The data analysis tool used multiple linear regression model, while hypothesis testing was done by F test and t test at five percent alpha Findings: The result reveal that the product variation and service quality had a significant simultaneous and partial effect on customer satisfaction, furthermore there is evidence the strong relationship between the variables of product variation and service quality with customer satisfaction Research limitations/implications: This research is only carried out in one company as the object of research. Further researchers can conduct research from several companies so that the study results can be generalized Practical implications: The results of this study will provide to the management and the company in increasing profitability through consumer satisfaction. The results of the study also provide theoretical implications as a reference in costumer satisfaction. Originality/value: Determine the effect of product variations and service quality either simultaneously or partially on customer satisfaction. Paper type: Research paper